Performance of reverse osmosis membrane as a bathroom wastewater filter - Permadi Adi; Dwi Jayanti Tamara; Reza Saputra Muhammad; Salsabila Hervia; Pink Audina Pink; Fitriyanto Edy (BIO Web of Conferences)
As the population in Indonesia increases, water pollution becomes increasingly uncontrolled. people who still think that direct disposal of greywater waste does not cause serious environmental problems. Currently, liquid waste can only be used for irrigation of plants, washing cars, washing windows and flushing toilets. the concept of reuse or reuse. However, this concept can help reduce the use of available clean water. This research aims to determine the performance of reverse osmosis (RO) membrane units for treating bathroom wastewater. In this study, bathroom waste was simulated using soapy water, shampoo water, urine and salt water. Where the waste water is pumped to the RO membrane unit. pH, iron metal (Fe), manganese (Mn), fluoride (F) and organoleptic parameters (smell, taste and color) were observed before and after entering the RO membrane unit. Test results on the shampoo showed that after going through the RO unit, the water became slightly more acidic while other parameters met clean water quality standards. The same test results also occurred in soapy water and salt water. Test results on filtered urine show that there is a reduction in acidity but the smell of urine is still present. Testing these parameters shows that the RO membrane unit has succeeded in maintaining the quality standards for Fe, Mn and F metal content in water even though there is a decrease in pH in soapy water, shampoo water and salt water. Based on these results, additional processing is still needed to return the pH of the water to the pH range of clean water and eliminate the urine Odor that still exists.